MANGERIAN FOUNDATIONS OF THE AUSTRIAN SCHOOL OF ECONOMICS AND THE AUSTRIAN BUSINESS CYCLE THEORY: LINKAGE AND CONTROVERSIES - Toth, András (REVISTA PROCESOS DE MERCADO, 2021)
The Austrian Business Cycle Theory (ABCT), based on the insights of Böhm-Bawerk and Mises, became one of the core theoretical insights of the Austrian School of Economics.The 2008 crisis seemed to support the ABCT. Nonetheless, the relatively small harm caused by the crisis and the longest economic expansion ever seen refuted warnings about hyperinflation and civilizational collapse. The aim of this paper is to explain the cause of the relative success of the credit expansion monetary system through the reconstruction of the original Mengerian theoretical framework combined with the Misesian insights.First, the paper reconstructs Carl Menger’s main tenets of thought. The paper discusses how the post-Mengerien development diverged into two conflicting concepts concerning the role of credit: the one conceptualized by Schumpeter and the one conceptualized by Mises. The paper shows how Schumpeter distorted the original Mengerian thought in order to explain business cycles, while Mises, under the influence of Böhm-Bawerk, discarded some of Menger’s key assumptions making ABCT less reflective of the impacts of the entrepreneurial boom allowed by credit expansion. In the discussion, I argue that the reformation of ABCT based on the combination of the original Mengerian framework and the Misesian insights explains both the resilience and success of the credit based monetary system, but also warns that the real danger is the rise of an omnipotent government based on credit expansion that can pave the road to serfdom. Keywords: Austrian Business Cycle Theory, Austrian School of Economics. JEL Classification: A10, B13, B53, D50, E14, E32, E58, P16xí.